Adaptive control with saturation-constrainted observations for drag-free satellites — a set-valued identification approach - Tan, Shuping; Guo, Jin; Zhao, Yanlong; Zhang, Jifeng (Science China. Information sciences, 2021)
The high-accuracy drag-free control is one of the key technologies for gravity gradient satellites. Since the range of the gravity gradiometer is limited, the measurement is subject to the saturation constraint. This paper introduces a design method of the adaptive drag-free control law by employing the set-valued identification approach. By inserting several thresholds in the constrained interval, the output observation is transformed into the set-valued information under different thresholds, based on which and the weighted optimization technique the identification algorithm for the unknown parameter is constructed. The adaptive drag-free control law is designed via the certainty equivalence principle. It is shown that the identification algorithm is strongly convergent and the convergence rate of the estimation error is obtained. The performance of the closed-loop system is analyzed, and the asymptotic optimality of the adaptive controller is proved. The numerical simulation is included to verify the effectiveness of the main results.